Methods of analysis of wood preservatives and treated timber. Quantitative analysis of preservative solutions and treated timber containing pentachlorophenol, pentachlorophenyl laurate, γ-hexachlorocyclohexane and dieldrin Part 6, (30th November 1983) - British Standards Institution,
No abstract available